Zawartość metali ciężkich w osadach antropogenicznych z obszaru starego miasta Szczecina = Content of heavy metals in anthropogenic sediments from area of old town Szczecin - Chudecka, Justyna; Tomaszewicz, Tomasz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In this work the anthropogenic sediments from area of Old Town Szczecin (Square of Orła Białego) were characterized. It was found that layer of these sediments had thickness of approx. 4 m and materials contained therein were enriched in organic matter, including humus. These sediments contained a huge amount of mechanical deposits which were dominated by building rubble that formed of 3-meter continuous rubble layer within the anthropogenic layer.
Keywords: grunty miejskie; osady antropogeniczne; zanieczyszczenia mechaniczne; uziarnienie; pH; materia organiczna; metale ciężkie; urban grounds; anthropogenic sediments; mechanical deposits; texture; organic matter; heavy metals